Primeros registros de los géneros Phyllopeltula y Reimnitzia (líquenes epífitos) para el Ecuador - BUSTAMANTE, ANDREA; GUSMÁN, ELIZABETH; BENITEZ, ANGEL (Gayana Botánica, 2018)
Phyllopeltula steppae and Reimnitzia santensis from dry forest of southern Ecuador were collected for the first time in Ecuador. The collections constitute the first records of the genera Phyllopeltula and Reimnitzia in the country. We provide information about ecology and distribution of the species.